Agreement between Cloposcopy and Pap smear in diagnosis of cervical lesions - Salman, Safa; Issa, Rana; Ibrahim, Ali (Latakia University Journal -Medical Sciences Series, 2018)
The research was conducted in the department of obstetrics and gynecology at Al-Assad and Tishreen university hospitals in Lattakia in the period between (1/6/2016) – (31/12/2016). The study included (100) patients, who submitted to Colposcopy and Papanicolaou smear and biopsy was taken if needed to evaluate the agreement between Cloposcopy and Pap smear in diagnosis cervical lesions.By evaluating Colposcopy and Pap smear as diagnostic means, the rate of abnormal Colposcopy was 27% while the rate of abnormal pap smear was 5%. The sensitivity of Colposcopy 85.71% was higher than the sensitivity of Pap smear 57.14%, and the specificity of Colposcopy 7.14% was lower than the specificity of Pap smear 92.85%.The statistical study has shown that: 1-We found a significant agreement between Pap smear and Histopathology (p=0.011<0.05). 2-We didn,t find a significant agreement between Colposcopy and Histopathology (p=0.599>0.05), but after using Reid Colposcopic Index(RCI) a significant agreement was found between RCI and Histopathology (p=0.028<0.05). 3-We found a significant agreement between RCI and Pap smear (p=0.000<<0.05). We conclude that Pap smear and Colposcopy are good and necessary screening tests for cervical cancer and pre cancer diagnosis. تقييم التوافق بين الموجودات التنظيرية لعنق الرحم مع لطاخة بابانيكولاو في تشخيص آفات عنق الرحم أجري البحث في قسم التوليد وأمراض النساء في مشفيي الأسد وتشرين الجامعيين باللاذقية في الفترة الواقعة بين (1/6/2016) – (31/12/2016). شمل البحث (100) مريضة, أجري لهن تنظير مكبر لعنق الرحم ولطاخة بابانيكولاو، كما تم أخذ خزع موجهة بالتنظير عند الحاجة. وذلك لتقييم التوافق بين الموجودات التنظيرية لعنق الرحم ولطاخة بابانيكولاو في تشخيص آفات عنق الرحم. وبتقييم التنظير المكبر لعنق الرحم ولطاخة بابانيكولاو كوسيلتين تشخيصيتين لآفات عنق الرحم تبين أن نسبة الحالات الشاذة بالتنظير المكبر27%، بينما نسبة الحالات الشاذة بالفحص الخلوي للطاخة بابانيكولاو5%. كما تبين أن حساسية التنظير المكبر 85.71% أعلى من حساسية اللطاخة 57.14%، ونوعية التنظير المكبر 7.14% أقل من نوعية اللطاخة 92.85%. وبالدراسة الإحصائية تبين ما يلي: 1-وجدت علاقة إحصائية بين لطاخة بابانيكولاو والفحص النسيجي (P=0.011<0.05). 2-لم يثبت وجود علاقة بين التنظير المكبر لعنق الرحم والفحص النسيجي(P=0.599>0.05)، لكن بعد استخدام مشعر ريد التنظيري RCI في قراءة الموجودات التنظيرية فقد وجدت علاقة إحصائية بينه وبين الفحص النسيجي (P=0.028<0.05). 3-وجدت علاقة إحصائية قوية بين مشعر ريد التنظيري (RCI) ولطاخة بابانيكولاو (P=0.000<<0.05). وهكذا نستنتج أن كل من لطاخة بابانيكولاو والتنظير المكبر لعنق الرحم وسيلتي مسح جيدتين وضروريتين يمكن الاعتماد عليهما في الاستقصاء الأولي عن الآفات السرطانية وما قبل السرطانية لعنق الرحم.